The relationship between mobilization and husband's support with the healing of post sectio secarea surgical wounds - Supriadi Supriadi; Erni Eka Sari Sari; Lindriani Lindriani (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Labor is a physiological process characterized by coordinated and effective involuntary uterine contractions that progressively cause cervical dilatation and effacement, followed by fetal descent, delivery of the baby, and expulsion of the placenta. Quality postpartum care for mothers after caesarean section (CS) plays an important role in efforts to reduce maternal morbidity and mortality. Aspects of care for post-CS mothers that need attention, in addition to monitoring vital signs, dressing changes, wound care, and administration of analgesics, include early mobilization and psychological support from the family, particularly from the husband as the partner. Purpose: To determine the relationship between mobilization and husband’s support and wound healing after caesarean section surgery. Method: This study used an analytical survey design with a cross-sectional approach. The population consisted of all postpartum mothers who visited Mapilli Public Health Center for post-CS wound care from April to July 2024, totaling 45 mothers. The sampling technique used was total sampling. Data were collected using questionnaires and a wound assessment observation sheet. The collected data were processed using SPSS version 23 and analyzed with the Chi-Square test. Results: The Chi-Square test showed a relationship between mobilization and post-CS wound healing with a p-value of 0.02 (< α = 0.05), indicating that Ha was accepted and Ho was rejected. Furthermore, the Chi-Square test for husband’s support yielded a p-value of 0.03 (< α = 0.05), which also indicates that Ha was accepted and Ho was rejected. Thus, there is a significant relationship between husband’s support and wound healing after caesarean section. Conclusion: The study demonstrates that both mobilization and husband’s support are associated with wound healing in mothers after caesarean section. The findings are expected to provide information and enrich references for delivering optimal care to postpartum mothers during their physical and psychological recovery period.